Suitable ultrasound screening method for older adults with disability to identify low muscle mass - Ding, Huaying; Lin, Xia; Huang, Sha; Liao, Jie; Li, Zhouyu; Chen, Lanlan; Zhu, Li; Xie, Yukuan; Nie, Qian; Chen, Xiaoyan (Frontiers in Medicine, 2023)
Objective: This study aimed to investigate the accuracy and consistency of different ultrasound protocols for the measurement of gastrocnemius muscle (GM) thickness and to identify a suitable ultrasound scheme that can be used to detect the low muscle mass in older with disability.In this cross-sectional study, each participant underwent three different ultrasound protocols for the measurement of the GM thickness, and each measurement was repeated three times. The three measurement schemes were as follows: method A, lying on the examination bed in a prone position with legs stretched and relaxed and feet hanging outside the examination bed; method B, lateral right side lying position with legs separated (left leg flexed and right leg in a relaxed state); and method C, right side lying position with legs together and lower limb muscles in a relaxed state. The low muscle mass was determined by averaging two or three measurements of the GM thickness determined using different sonographic protocols.The study included 489 participants. The difference in the prevalence of low muscle mass identified between two and three replicates of the same measurement protocol ranged from 0 to 1.3%. Considering the three repeated measurements of the method A as the reference, the area under the curve (AUC) in different measurement schemes were 0.977-1 and 0.973-1in males and females, respectively. Furthermore, male and female Kappa values from low to high were 0.773, 0.801, 0.829, 0.839, and 0.967 and 0.786, 0.794, 0.804, 0.819, and 0.984, respectively.Conclusions: Different ultrasound measurement protocols showed high accuracy and consistency in identifying low muscle mass. Repeating the measurements two or three times was found to be feasible.